"Wild in My Eyes": An Analysis of Narratives and Narrative Identities among Diverse Drug Users. Issue 12 (2nd December 2022) - Erickson, Jacob H.
ABSTRACT: There is little research examining how race, class, gender, and residential location work simultaneously to inform drug using identities. Using insights from narrative criminology, I build upon this literature by providing an examination of 58 current or former users interviewed across two research sites. Participants pulled from various cultural and subcultural narratives to construct narrative identities shaped by behavior, race, class, gender, and residential location. The primary identities constructed included "party user, " "chill user, " and "addict." Intersecting social identities shaped how participants constructed identities in relation to their drug use in nuanced and complex ways. I provide evidence of how deviant identities are shaped by intersectional influences and how such influences limit the narratives available for deviant actors to construct identities.